Uncertainty in deliberate lexical interventions Exploring Esperanto speakers' opinions through corpora - Maradan, Mélanie (Sprachwissenschaft, 2020)
Language managers in their different forms (language planners, terminologists, professional neologists ...) have long tried to intervene in the lexical usage of speakers, with various degrees of success: Some of their lexical items (partly) penetrate language use, others do not. Based on electronic networks of practice of the Esperanto speech community, Mélanie Maradan establishes the foundation for a new method to extract speakers' opinions on lexical items from text corpora. The method is intended as a tool for language managers to detect and explore in context the reasons why speakers might accept or reject lexical items. Mélanie Maradan holds a master's degree in translation and terminology from the University of Geneva/Switzerland as well as a joint doctoral degree in multilingual information processing and philosophy (Dr. phil.) from the universities of Geneva and Hildesheim/Germany. Her research interests include planned languages (Esperanto studies) as well as neology and corpus linguistics. She works as a professional translator and terminologist in Switzerland.